A Biological Basis for the Gender Wage Gap: Fecundity and Age and Educational Hypogamy - Solomon Polachek; Xu Zhang; Xing Zhou (Institute for the Study of Labor (IZA), 2014)
This paper shows how a shorter fecundity horizon for females (a biological constraint) leads to age and educational disparities between husbands and wives. Empirical support is based on data from a natural experiment commencing before and ending after China's 1980 one-child law. The results indicate that fertility in China declined by about 1.2-1.4 births per woman as a result of China's anti-natalist policies. Concomitantly spousal age and educational differences narrowed by approximately 0.5-1.0 and 1.0-1.6 years respectively. These decreases in the typical husband's age and educational advantages are important in explaining the division of labor in the home, often given as a cause for the gender wage gap. Indeed, as fertility declined, which has been the historical trend in most developed countries, husband-wife age and educational differences diminished leading to less division of labor in the home and a smaller gender wage disparity. Unlike other models of division of labor in the home which rely on innately endogenous factors, this paper's theory is based on an exogenous biological constraint.
Keywords: J1; J2; J3; J43; J7; J8; N3; N9; O5; Y8; Z13; 330; gender wage gap; marital patterns; age at marriage; husband-wife age gap; husband-wife educational gap; homogamy; division of labor in the home; household economics